"WITHOUT THINKERS … NO THEORIES OF THE WORLD"1. Issue 1 (February 2016) - Mitrović, Branko
ABSTRACT: Tim Crane's books Aspects of Psychologism and The Objects of Thought present a perspective on human intentionality based on internalism about mental contents. Crane understands intentionality as the defining aspect of the mental. The theory of intentionality that he formulates is similar to that of John Searle when it comes to ontological commitments, but it is also marked by a more traditional approach that retains the concept of intentional objects as its central aspect. In this review I examine the implications of Crane's internalism for the philosophy of history, by comparing his views with some well‐known arguments in favor of externalism about mental contents, such as Hilary Putnam's "Twin Earth" and Tyler Burge's "arthritis" mental experiments. Although internalism about mental contents such as Crane's is a minority view among contemporary analytic philosophers, I argue that it has significant advantages when it comes to the philosophy of history, because it is much better aligned with standard interpretive procedures in historical research. At the same time, externalism about mental contents typically results in inappropriate contextualizations and approaches that most practicing historians will find awkward. More generally, it is possible to argue that over decades, analytic philosophers' externalist tendencies have significantly contributed to the reduced interest in their views among philosophers of history. The final section of the article reviews the implication of Crane's views on nonconceptual contents of human perception for art historiography.